2001
DOI: 10.1002/1531-8249(200101)49:1<117::aid-ana19>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

SCA12 is a rare locus for autosomal dominant cerebellar ataxia: A study of an Indian family

Abstract: Spinocerebellar ataxia 12 (SCA12) is an autosomal dominant cerebellar ataxia (ADCA) described in a single family with a CAG repeat expansion in the PPP2R2B gene. We screened 247 index cases, including 145 families with ADCA, for this expansion. An expanded repeat ranging from 55 to 61 triplets was detected in 6 affected and 3 unaffected individuals at risk in a single family from India. The association of the PPP2R2B CAG repeat expansion with disease in this new family provides additional evidence that the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 0 publications
4
37
4
Order By: Relevance
“…The repeat length ranged from 8-23 triplets in normal individuals. Anticipation, which was not detected in previous analyses (Fujigasaki et al 2001;O'Hearn et al 2001;Srivastava et al 2001;Holmes et al 2003), was also not observed in this larger study. The age at onset of the disease ranged from 26 to 56 years (mean 40.2 years) and the duration of illness at the time of examination varied from 1 to 22 years.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…The repeat length ranged from 8-23 triplets in normal individuals. Anticipation, which was not detected in previous analyses (Fujigasaki et al 2001;O'Hearn et al 2001;Srivastava et al 2001;Holmes et al 2003), was also not observed in this larger study. The age at onset of the disease ranged from 26 to 56 years (mean 40.2 years) and the duration of illness at the time of examination varied from 1 to 22 years.…”
Section: Resultscontrasting
confidence: 76%
“…This has been attributed to the ethnicity, diversity and inherent genetic differences between sub-populations. SCA12, first reported in a large American pedigree of German descent (Holmes et al 1999;O'Hearn et al 2001) has been subsequently reported only in Indian families (Fujigasaki et al 2001;Srivastava et al 2001). In an earlier study, expansion in the PPP2R2B gene was reported in 6 patient, and 3 asymptomatic at-risk individual, in 5 Indian families (Srivastava et al 2001), which suggested that SCA12 is not rare in India.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In SCA1, SCA2, and SCA3, gait ataxia is the most common symptom at onset. For SCA12, hand tremor is the earliest feature of the disease but there are a few cases in which gait ataxia is the presenting symptom, a feature which has not been observed in previous studies [Bahl et al, 2005;Fujigasaki et al, 2001;Holmes et al, 1999;Srivastava et al, 2001].…”
Section: Analysis Of the Variations In Sca-lsvdmentioning
confidence: 78%
“…Similar features occur in SCA8, in addition to saccadic dysmetria (Day et al, 2000;Koob et al, 1999), and SCA10 (Zu et al, 2000;Grewal et al, 2002;Lin & Ashizawa, 2005). SCA11 is associated with horizontal and vertical nystagmus as well as jerky pursuit (Worth et al, 1999), while approximately one third of SCA12 patients can develop saccadic slowing, abnormal smooth pursuits or pathological nystagmus (Worth et al, 1999, Fujigasaki et al, 2001. Besides, in subjects affected with SCA13 is usual to observe horizontal nystagmus (Stevanin et al, 2005;Waters & Pulst, 2008).…”
Section: Other Spinocerebellar Ataxiasmentioning
confidence: 99%